Low voltage DC power supply with spike-blocking features - Torla, A. Lutfi; Khan, Sheroz; Abdul Muthalif, Asan Ghani; Azman, Amelia Wong; Mustafah, Yasir Mohd. (2013)
RFID tags, sensors embedded with buried devices and biomedical implants all operate at low voltage levels due to power limitations. The ever increasing use these embedded devices has also created a demand in the industry for lowvoltage power supplies. Since many of these circuits are mobile in nature and so are bound to operate in many different environments, the power supply must also be capable of ensuring a stable voltage output even under adverse conditions. This paper analyzes and simulates a power supply circuit that promises a low ripple factor with an element of spike-blocking capability. It centers on a phase-modulation technique that effectively cancels out 99.6% of ripples when operating with a 100 mV ac input at a frequency of 10 kHz. This active noise-cancellation technique allows for a more stable voltage output. It also has a limited inbuilt capability to block spikes. A 100 mV injected spike is brought down to only 6 mV without the use of other damping circuits. This work is therefore capable of damping a large part of the variations in the input voltage, even at low voltages.